Congenital Ocular Motor Apraxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The clinical and neuroradiological findings, and long-term intellectual prognosis in 10 patients (4 boys and 6 girls) with congenital ocular motor apraxia (COMA) are reviewed by researchers at Tottori University, Yonago, Japan.